TAMI-12. CANCER STEM CELL ENRICHMENT AND METABOLIC SUBSTRATE ADAPTABILITY ARE DRIVEN BY HYDROGEN SULFIDE SUPPRESSION IN GLIOBLASTOMA. (9th November 2020) - Silver, Daniel; Roversi, Gustavo; Bithi, Nazmin; Neumann, Chase K; Troike, Katie; Ahuja, Grace; Reizes, Ofer; Brown, J Mark; Hine, Christopher; Lathia, Justin
Abstract: Glioblastoma (GBM) remains among the deadliest of human malignancies. The emergence of the cancer stem cell (CSC) phenotype represents a major challenge to disease management and durable treatment response. The extrinsic, environmental, and lifestyle factors that result in CSC enrichment are not well understood. The CSC state endows cells with a fluid metabolic profile, enabling the utilization of multiple nutrient sources. Therefore, to test the impact of diet on CSC enrichment, we evaluated disease progression in tumor-bearing mice fed an obesity-inducing high-fat diet (HFD) versus an energy-balanced, low-fat control diet. HFD consumption resulted in hyper-aggressive disease that was accompanied by CSC enrichment and shortened survival. HFD consumption also drove intracerebral accumulation of saturated fats, which in turn inhibited the production and signaling of the gasotransmitter hydrogen sulfide (H2 S). H2 S is an endogenously produced bio-active metabolite derived from sulfur amino acid catabolism. It functions principally through protein S-sulfhydration and regulates a variety of programs including mitochondrial bioenergetics and cellular metabolism. Inhibition of H2 S synthesis resulted in increased proliferation and chemotherapy resistance, whereas treatment with H2 S donors led to cytotoxicity and death of cultured GBM cells. Compared to non-cancerous controls, patient GBM specimens were reduced in overall protein S-sulfhydration, which was primarily lost from proteins regulating cellular metabolism. These findings support the hypothesis that diet-regulated H2 S signaling serves to suppress GBM by restricting metabolic adaptability, while its loss triggers CSC enrichment and disease acceleration. Interventions augmenting H2 S bioavailability concurrent with GBM standard of care may improve outcomes for GBM patients.